“I’d Rather Do It Single-Handed”—Nursing Students’ Struggles with Group Assignments: A Qualitative Study - Aimei Mao; Pak-Leng Cheong; Iat-Kio Van; Hon-Lon Tam (Education Sciences, 2023)
This study, framed by the GRPI (Goal, Role, Process, and Interaction) teamwork model, explores team dynamics among nursing students in performing group assignments, utilizing a qualitative research design. Twenty-three nursing students from Year 1 to Year 4 at a nursing school in Macau were invited. Semi-structured personal interviews were carried out. In addition, three teachers who were involved in instructing and assessing group assignments of nursing students were also interviewed. Data were analyzed using inductive and deductive approaches. The study found that although the barriers to accomplishing effective teamwork were embedded into the four dimensions of the DRPI model, they were interplayed. Communication was fundamental for teamwork, thus leading to a modified DRPI model. Teammates did not equally share the workload. Despite interpersonal conflicts among teammates, nursing students managed to stay in superficial harmony with their peers. They became more familiar with teamwork while advancing into their senior years but with decreased group communications. This study highlights various factors preventing students from transferring individualism to team players. Teaming is not an equal learning opportunity for teammates. Culturally upheld value of harmony prevails in the interpersonal relationships of the team members, which may compromise the teamwork spirit cultivation expectations from the teachers.